Extratos de brássicas e termoterapia no controle de podridão parda em pós-colheita de pêssego - Pazolini, Kelly (2014)
Brown rot (Monilinia fructicola) is the major disease of stone fruits, causing pre and postharvest losses. The objectives of this study were to evaluate different forms of extraction of canola and indian mustard extracts to control brown rot, assess the best way of application of extracts of these plants associated with thermotherapy to control brown rot and compare the best result of these studies with chemical control. Initially, tests were made with different forms of extraction of canola and indian mustard extracts. For this, brassica species were collected in full bloom, oven dried and ground to obtain a powder. For the simple extraction mode, the powder was mixed with water and filtered. For maceration extraction, the extract was filtered only after a time of 8 hours of booking. To infusion extract, was used water heated to 100 °C and after 20 min the solution was filtered. Simple extracts from each plant were selected to be tested in different combinations with the thermotherapy treatment by immersion in hot water (50 °C for 30 s). The treatments tested for canola and indian mustard were: 1- Application of the respective extract and inoculation of fruits (EI); 2- inoculated fruits and implementation of its extract (IE); 3- Inoculation of fruit and application of thermotherapy (IT); 4- Application of the respective extract, inoculation of fruits and application of thermotherapy (EIT); 5- Inoculation of fruit, application of thermotherapy and application of the extract (ITE); 6- Application of the respective extract, inoculation of fruits, application of thermotherapy and application of the extract again (EITE) and 7- inoculated peaches and treated with sterile water (control). The EITE with treatments canola and indian mustard were selected for comparison with chemical treatment (azoxystrobin®, 2 g L-1). All tested extraction, of the two species of brassica, significantly reduced the mycelial growth and conidial germination of M. fructicola, and the area of brown rot injury and conidia production in vivo, except the extraction infusion of indian mustard, that did not reduce the area of brown rot injury. The EITE treatments of canola and indian mustard were more efficient in controlling brown rot in peach, reducing the disease, on average, 58 and 51%, respectively. When the treatments were compared with chemical control, were observed that canola EITE treatment was superior to indian mustard EITE treatment, and did not differ from chemical control on the production of conidia in brown rot lesions in peach, reducing the area of the lesion in more than 84% and sporulation in more than 90%. The application of simple canola extract, whether used alone or in EITE tactic, is an efficient alternative in the control of brown rot in peach postharvest.